KETERAMPILAN PEMECAHAN MASALAH KOLABORATIF SISWA SMP YANG BERBEDA ADVERSITY QUOTIENT PADA MATERI SEGIEMPAT - Erfi Hannania; Tatag Yuli Eka Siswono; Endah Budi Rahaju (IKIP Siliwangi, 2022)
This study aims to describe the collaborative problem solving skills of students SMP with category quitter, camper, dan climber on quadrilateral. Three subjek were selected through adversity response profile questionnaire. The instruments used are problem solving test, observation sheet and interview. The results showed that collaborative problem solving skills at the stage of exploring and understanding the problem, quitter student abilities needed assistance from camper dan quitter students to understand the problems in the problem solving test so that information transfer occurred between group friends. After getting help, at the stage of representing and formulating quitter students can identify and describe problem solving tests in their own language, while camper and climber students do not experience problems in representing and formulating the tests given. At the stage of planning and implementing the camper and climber students communicate about the plans and actions that are being or will be taken. However, quitter students do not communicate about plans and actions that are being or will be taken. At the monitoring and evaluating stage, quitter, camper and climber students monitor the results of their actions and evaluate each other's solutions that have been obtained. At this stage, camper students produce different solutions, and climber students correct these solutions.